(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
The assignment problem is a fundamental combinatorial optimization challenge with applications across industries, where resources must be assigned to tasks in a cost-efficient manner. Traditional approaches, such as the Hungarian algorithm, minimize assignment costs by reducing the matrix to an optimal form. This study introduces an alternative approach using an "absolute difference calculation" algorithm, in which each element’s difference from the minimum or maximum in its row is evaluated and adjusted iteratively to ensure feasible solutions and finally MATLAB program is used to solve example.